THE COMPOTITION OF TRAPS FISHING CATCHES AT THE FISH AGREGATING DEVICE (FAD’s) IN TELUK RHU VILLAGE, IN NORTH RUPAT DISTRICT, BENGKALIS REGENCY OF RIAU PROVINCES - Wemphy Hernando; Arthur Brown; Alit Hindri Yani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted on January 25th to February 3 th 2016 in Teluk Rhu Village Bengkalis Regency Of Riau Provinces. This research aims to analyze the composition of traps catches and determine the type and amount of catches in the morning and afternoon at the Fish Agregating Device (FAS’s). The method used in this research is a survey and research conducted for 10 consecutive days. The catches during of research were 1,495 kg (65 ekor). The results of research on the composition of traps catches in the morning is 0,485 kg (25 fishes), while during the afternoon 1,01 kg (40 fishes). The catches is consists of four species, namely: Pseudocienna amovensis, Stromateus cinereus, Equulites leuciscus, and Chorine mustala. Afternoon catches is bigger than morning catches.Keywords: Fish agregating device(FAD’s), Teluk Rhu village, Traps fishing